Identifikasi Genera Nematoda pada Lahan Perkebunan Karet (Hevea braziliensis) di Desa Santan Ulu Kecamatan Marangkayu Kabupaten Kutai Kartanegara - Doni Fiyan (Mulawarman University, 2019)
This study aims to determine the dominant nematode genus and nematode population associated with rubber plants. Field research were carried out in Santan Ulu Village, Marangkayu District, Kutai Kartanegara Regency. The laboratory works was carried out at the Laboratory of Plant Pest and Disease Sciences, Faculty of Agriculture, Mulawarman University. The study was conducted for 3 months from October to December 2017. The method in this study is a diagonal method on nine rubber trees that have produced. The obtained nematodes were identified and calculated by the population of each genus. The results showed that there are five species of nematodes in rubber plantation areas aged 5, 7 and 10 years, namely Aphelenchulus, Dorylemus, Pratylencus, Rhabditis, and Rotylenchulus. Weeds that grow on rubber plantations, namely, Imperata cylindrica L, Mikania micranta, Melastoma offine, Chromolaena odorata, and Paspalum conjungtum.